Words and visions around/about Chinese transnational mobilities 流动 - Pedone, Valentina; Castorina, Miriam (Studi e saggi, 2023)
This collection gathers the contributions of ten scholars on the topic of transnational cultural and physical mobility originating in China. These contributions aim to open conversations among Chinese Studies scholars by applying a Mobility Studies perspective. Exploring diverse narratives and forms of representation from people of Chinese heritage, the book is divided into three parts that each look closely at the relationship between movement and cultural production. The first part is dedicated to four types of mobility of people from China to Italy, namely tourist mobility (Miriam Castorina), labor mobility (Valentina Pedone), student mobility (Xu Hao), and mobility of social elites (Andrea Scibetta). The second part is dedicated to examples of reverse mobility from Italy to China (Gao Changxu, Chiara Lepri, Giuseppe Rizzuto). The third part focuses on case studies based on mobilities from China to territories other than Italy (Rebecca Ehrenwirth, Martina Renata Prosperi, Giulia Rampolla).